Revitalization of small millets for nutritional and food security by advanced genetics and genomics approaches - Lydia Pramitha, J.; Ganesan, Jeeva; Francis, Neethu; Rajasekharan, Ravikesavan; Thinakaran, Jenita (Frontiers in Genetics, 2023)
Small millets otherwise termed as Nutricereals are smart foods and they are expected to overrule the food industries and diets in future for attaining nutritional security. They are climate resilient and nutritious in nature. Nowdays, small millet based foods are becoming popular in markets and they are preferred as a desirable food for celiac and diabetic patients. These crops were once ruling the countries for food and fodder while shift in dietary habits to staple crops pushed them out of the mainstream cultivation during green revolution. Nevertheless, small millets are rich in micronutrients and essential amino acids for regulatory activities. Hence, recent ventures on bringing back these lost crops for their desirable emoluments are being undertaken by International and National Organizations across countries. The major concern on reviving these crops is to boost the immune system of the upcoming generations to tackle emerging pandemics and disease infestations. Earlier periods of civilization consumed these crops and also they had a greater significance in the ethnobotanical values. Along with nutrition these crops also possess therapeutic traits and recorded a vast medicinal use in the tribal communities for treating diseases like cancer, heart attack and gastrointestinal issues. Therefore, this review highlights the complete significance of small millets and their values in cultural heritage. Further this would enlighten the focus to dissect the nutritional and therapeutic traits in small millets for developing a sustainable diet in near future.